ANALISIS FRAMING BERITA PARIWISATA PADA TELEVISI LOKAL: STUDI KASUS JOGJA TV DI YOGYAKARTA DAN AGROPOLITAN TV DI JAWA TIMUR - Eka Yonavilbia (Majalah Ilmiah Bijak, 2016)
The main research objective is to understand the tendency of of news framing ideology - idealism or commercialism of two local TV, Jogja TV and Agropolitan TV. This media study was carried out using Etman’s framing analysis. method concerning 16 local news and  one non-local news broadcasted on August 2009. The research results showed that there were the ideological differences of tourism local news framing  broadcasted in the both local TV.Jogja TV more inclined to commercialism as promotion on local tourism managed by private company. Meanwhile Agropolitan TV tended to idealism. Regarding the non–local program of tourism, the Jogja TV’ editors inclined to idealism as part of social responsibility of local TV stations.